First-class – biosynthesis of 6-MSA and bostrycoidin type I polyketides in Yarrowia lipolytica - Bejenari, Mihaela; Spedtsberg, Eva Mie Lang; Mathiesen, Julie; Jeppesen, Alexandra Claire; Cernat, Lucia; Toussaint, Aouregane; Apostol, Cristina; Stoianov, Victor; Pedersen, Tobias Bruun; Nielsen, Mikkel Rank; Sørensen, Jens Laurids (Frontiers in Fungal Biology, 2024)
Fungal polyketides are a large group of secondary metabolites, valuable due to their diverse spectrum of pharmacological activities. Polyketide biosynthesis in filamentous fungi presents some challenges: small yield and low-purity titers. To tackle these issues, we switched to the yeast Yarrowia lipolytica, an easily cultivable heterologous host. As an oleaginous yeast, Y. lipolytica displays a high flux of acetyl- and malonyl-CoA precursors used in lipid synthesis. Likewise, acetyl- and malonyl-CoA are the building blocks of many natural polyketides, and we explored the possibility of redirecting this flux toward polyketide production. Despite its promising prospect, Y. lipolytica has so far only been used for heterologous expression of simple type III polyketide synthases (PKSs) from plants. Therefore, we decided to evaluate the potential of Y. lipolytica by targeting the more complex fungal polyketides synthesized by type I PKSs. We employed a CRISPR-Cas9-mediated genome editing method to achieve markerless gene integration of the genes responsible for bostrycoidin biosynthesis in Fusarium solani (fsr1, fsr2, and fsr3) and 6-methylsalicylic acid (6-MSA) biosynthesis in Aspergillus hancockii (6MSAS). Moreover, we attempted titer optimization through metabolic engineering by overexpressing two enzymes, TGL4 and AOX2, involved in lipid β-oxidation, but we did not observe an effect on polyketide production. With maximum titers of 403 mg/L 6-MSA and 35 mg/L bostrycoidin, the latter being substantially higher than our previous results in Saccharomyces cerevisiae (2.2 mg/L), this work demonstrates the potential of Y. lipolytica as a platform for heterologous production of complex fungal polyketides.